(untitled) (Strathmore Law Review, 2016)
The war on terror is indeed justified. Terror attacks have resulted in the deaths of many innocent people around the world. Every nation in fact has a duty to protect her citizens from terror attacks and put up measures to prevent and punish terrorists. However, the government also has a duty to uphold the rule of law at all times despite the gravity of the attacks. This paper disputes arguments that terrorism is so novel and so grave that the rule of law can be sacrificed in order to deal with it. This position fails since terrorism is not a novel challenge and further because terrorism manifests itself as a form of imperialism, which is a challenge that has several times been dealt with in world history. Terrorism does not change the normal rules of criminal procedure and thus the rule of law should not be suspended in the name of counter-terrorism.